The pedagogical aspects of developing methodological support for distance learning study of the programming language C# - Yaschun, T. V.; Gromov, E. V. (Problems of Engineer-Pedagogical Education, 2018)
The impetuous informatization of society has led to a broad development of the ITindustry. For today, IT-workers have stable and decently paid jobs. One of the vacancies that are in demand in the IT-sphere is a programmer with the knowledge of the C# language. To work in the IT-industry in the area of program development with C#, you need to be proficient in the C# language. The authors developed an e-learning tutorial for learning the basics of programming in C# at a distance. It is intended to help beginners. The structure of the tutorial corresponds to the general pedagogical requirements for the development of teaching aids of this type. The tutorial consists of three main sections: training, control and statistical data collection. The "Training" section contains educational information, which is provided in text and multimedia form. The "Control" section consists of both the training control presented by the questions after each topic, and a final general test. In the statistics collection section, information on the results of the quiz is accumulated in the MS Access database. Such information may, if necessary, be reviewed and processed by the instructor. The authors believe that this development is relevant and promising. The tutorial can be useful in the real learning process, with distance learning and during the independent work of students.